Evaluating effectiveness of teaching / Sick Goh Ngong - Sick, Goh Ngong (Institut Teknologi Mara Cawangan Sarawak, 1989)
Institut Teknologi Mara is going to introduce a new system of evaluation for its academic staff effective 1989. The annual evaluation programme evaluates basically the following areas of an academic staff member: * Effectiveness of Teaching * Social Commitment * Research and Publication * Administrative Responsibilities * Personality An academic staff member, therefore is expected to perform the roles of a lecturer, educator, researcher, administrator as well as providing a model of exemplary personality. After the evaluation the staff member is assigned a number on an arbitrary scale of 1 to 15 with 1 being least satisfactory and 15 being most satisfactory. The performance status of the staff may be regarded as unsatisfactory (tidak memuaskan) or excellent (cemerlang), from one end of the scale to the other, depending on the score on the scale in terms of the areas under evaluation.